The Behavior of Price Multiples in India (1990-2007) - Sanjay Sehgal; Asheesh Pandey (Asian Academy of Management Journal of Accounting and Finance, 2009)
In this paper, we examine the behaviour of price multiples in India from 1990–2007. The distributions of price multiples tend to be normal over our study period, thus making the mean and standard deviation of these multiples relevant parameters for equity analysis in the Indian context. Further, sectors with high price multiples exhibit greater volatility in these multiples. This may result in greater price forecast errors for these sectors. We also find a very weak relationship between price multiples and their fundamental determinants. The cross-sectional linear models do not seem to be good descriptors of price multiples. However, price-to-book value (P/BV) and price-to-sales (P/S) ratios do reflect corporate fundamentals in the case of the Bombay Stock Exchange Sensitive Index, which tracks 30 stocks that are large in size and account for a major part of trading activity. In contrast, the fundamental determinants do not seem to drive price-to-earnings (P/E) and price-to-cash flow (P/CF) ratios, even for our limited universe of index stocks. This may be owing to the fact that earnings multiples are more driven by sentiments due to the actions of noise traders than by fundamentals, which influence the behaviour of value traders. Further, earnings are a bottom line number and thus are severely affected by accounting biases and judgments. The price multiples also seem to be sensitive to market conditions and therefore are generally greater in upturns, with the exception of infrastructure-related sectors. Our results are relevant for market stakeholders, who use price-multiple information for strategy building and policy decision making.